Emplacing Christ: An Indigenous Australian Ethics of Placemaking Across Borders. Issue 1 (2nd January 2018) - Eickelkamp, Ute
ABSTRACT: Travelling from my old heimat, Germany, I joined in September 2015 a group of An angu Pitjantjatjara Bible translators on a two-week long pilgrimage to the Holy Land. This journey offered further probing into An angu attachments to place that, until then, I had only known through ethnographic research in their desert homelands in northern South Australia. In the present article, I explore how and why the An angu Christians forged links with biblically inscribed places to which they had no ancestral ties. What they did bring is a deep-seated sense of emotional connection with Jesus abiding in heaven, and here the pilgrimage was a chance to anchor this relationship in his land – to emplace Christ. Notable in this process of shifting the presence of Jesus from heaven to earth was the pilgrims' moral concern to keep separate the emplaced stories of their ancestral lands on one hand, and the grounded narratives of the Christian Scriptures on the other. In Jonathan Mair and Nicholas Evans' terms, their approach was one of 'incommensuration', a strategy to avoid moral conflict by refusing to make comparisons between religious traditions. My article may thus be read as an ethnographic contribution towards the understanding of an Australian Indigenous ethics of placemaking across borders.